Pengembangan Lanjut Sistem Informasi Pelayanan Dan Pendataan UMKM Provinsi Riau (Kasus Dinas Perindustrian, Perdagangan, Koperasi Usaha Kecil Dan Menengah Provinsi Riau) - Siswanto, Didik; Darmayunata, Yuvi; Zamzami, Z; Febriadi, Bayu (LPPM STIKOM Tunas Bangsa, 2023)
Based on the previous authors, it was concluded that the Department of Industry, Trade, Small and Medium Enterprises Cooperatives of Riau Province had limitations in collecting data on the status of MSMEs that had attended training or had not attended training, making the government's training incomplete and not on target. Efforts have been made to develop an information system that can verify MSME data using optical character recognition to record MSMEs that are spread across Riau Province has a lack of features so that the government can manage all products uploaded by MSME actors and MSME actors can register with a registered NIK. Application of Services and Data Collection for UMKM in Riau Province This further research includes developing features according to the analysis to the Disperindagkop UKM. The conclusion from the results of the development of this information system has successfully developed a feature where MSME actors cannot register with the same NIK, there is a feature so that the admin can manage all products that have been uploaded by MSME actors, product data collection where currently there is a product category that is produced by MSMEs and the categories of each type of service prepared so that it is hoped that it will make it easier for users to operate the information system.